Understanding Gender Roles among Microenterprises: An Emphasis on Entrepreneurial Activities - Mendoza, Xavier Lawrence; Tadeo, Jerico B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Entrepreneurship has proven to become a potent economic opportunity augmenting activity that transcends the economic status quo, social strata, and even gender classification. Hence, the researchers aimed to understand gender roles among micro-enterprises in General Trias City and Tanza, Cavite, as a baseline study in undertaking gender-sensitive approach analysis to the enterprise. The study used descriptive design and purposive sampling methods in selecting 30 female and 30 male respondents in General Trias City and Tanza, Cavite. Findings showed that microenterprise business owners were dominated by 20 to 23 years old in both sexes, mostly single college undergraduates and having more than three years in operation. The study revealed the majority of male and female participants answered variably concerning gender roles among entrepreneurs in terms of; conflict management, mindset creation, emotion setting, planning, leading, organizing, controlling, and directing. On the other hand, 60 participants answered variably in participation roles among entrepreneurs in terms of; conflict management, mindset creation, emotion setting, planning, leading, organizing, controlling, and directing. Hence, the researchers' recommendations arrived at through gender roles analysis using the gender role attitude scale and degree of gender participation-role among entrepreneurs crafted towards the promotion of harmonious activities within enterprises concerning specific gender roles and their respective enterprise activities.